Immune Response to Hepatitis B Virus Vaccine in Term and Preterm Babies Received as per EPI Schedule (Bangladesh Journal of Child Health, 2010)
Objective: To determine the immune response of hepatitis B virus (HBV) vaccinegiven according to EPI schedule and to compare the antibody response among termand preterm babies.Setting: EPI centre, Paediatric OPD and Department of Virology, Bangabandhu SheikhMujib Medical University (BSMMU).Duration: May 2006 to April 2007.Study Population: Thirty preterm and thirty term babies who received 3 doses of HBVvaccination according to EPI schedule.Outcome variables: Immune response to HBV vaccine according to gestational age, accordingto birth weight and comparison of immune response among term and preterm babies.Results: Thirty three percent infants were non-responder in all the groups and 50%infants were good responders in 34-36 weeks and above. Total response was 80%among preterm and 86.6% among term infants.Conclusion: Most of the infants showed positive immune response and there was nosignificant difference among term and preterm babies.Key words: Efficacy of HBV vaccine; immune response; poor responder; good responder.DOI: 10.3329/bjch.v33i1.5668Bangladesh Journal of Child Health 2009; Vol.33(1): 1-5